2021
DOI: 10.1371/journal.pgen.1009699
|View full text |Cite
|
Sign up to set email alerts
|

OsMADS23 phosphorylated by SAPK9 confers drought and salt tolerance by regulating ABA biosynthesis in rice

Abstract: Some of MADS-box transcription factors (TFs) have been shown to play essential roles in the adaptation of plant to abiotic stress. Still, the mechanisms that MADS-box proteins regulate plant stress response are not fully understood. Here, a stress-responsive MADS-box TF OsMADS23 from rice conferring the osmotic stress tolerance in plants is reported. Overexpression of OsMADS23 remarkably enhanced, but knockout of the gene greatly reduced the drought and salt tolerance in rice plants. Further, OsMADS23 was show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 77 publications
(112 reference statements)
1
53
0
Order By: Relevance
“…Water loss was calculated from the decrease in the fresh weight compared with time zero. The average water loss rate was calculated from three independent experiments [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…Water loss was calculated from the decrease in the fresh weight compared with time zero. The average water loss rate was calculated from three independent experiments [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…This may provide a genetic basis to understand drought resistance mechanisms in other plants. Similarly, Li et al [121] showed that OsMAD23 serves as a positive regulator for altering ABA biosynthesis to enhance drought tolerance in rice. OsMAD23 encourages endogenous ABA accumulation through its biosynthesis and proline accumulation by activating several ABA and proline biosynthesis genes including OsNCED2/3/4 and OsP5CR.…”
Section: Molecular Mechanism Of Aba-mediated Drought Regulationmentioning
confidence: 95%
“…The malondialdehyde (MDA) content was determined with Keming’s MDA Detection Kit (micromethod; Suzhou Comin Biotechnology, Jiangsu, China), and the experiment was performed in triplicate. Seedling survival was evaluated on day 7 of the recovery culture [ 48 ]. For the soil-based drought tolerance experiments, the WT and OE-6 (transgenic rice line) seedlings were transferred to soil.…”
Section: Methodsmentioning
confidence: 99%